Investigation of a unilateral pleural effusion: What CT scan coverage is optimal?. Issue 6 (26th March 2020) - Syer, Tom; Arnold, David T; Patole, Sonia; Harvey, John; Medford, Andrew; Maskell, Nicholas A; Edey, Anthony
Abstract : The use of thoracic CT for patients presenting with a unilateral pleural effusion is well established. However, there is no consensus with regard to the inclusion of the entire abdomen and pelvis in the initial imaging protocol. In this prospective UK-based study, 249 patients presenting with a unilateral effusion had a CT thorax/abdomen/pelvis performed. The prevalence of malignancy on thoracic CT was 56% (140/249). Clinically significant findings below the diaphragm were identified in 59 patients (24%). Integrating this approach into standard practice allows more rapid identification of the primary malignancy, upstaging lesions or alternative sites for biopsy.